2005
DOI: 10.1207/s15548430jlr3703_2
|View full text |Cite
|
Sign up to set email alerts
|

Do Children Who Read More Books Know “What is Good Writing” Better than Children Who Read Less? A Comparison between Grade Levels and SES Groups

Abstract: Children's reading experiences are important for their academic achievement and literacy levels. Stanovich (2000) has asserted that "out-of-school reading experiences were the cause of certain 'rich get richer' effects in a variety of cognitive skills" (p. 245). Children exposed to reading from an early age and who start school with good reading levels also acquire reading and writing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…We excluded print exposure studies that reported no child outcomes or outcomes other than comprehension and technical reading and spelling skills, such as science tests or social ability tasks (e.g., Bråten et al, 1999; Burgess, 2005; Castles, Datta, Gayan, & Olson, 1999; Chomsky, 1972; Curry, Parrila, Stephenson, Kirby, & Catterson, 2004; Korat & Schiff, 2005; Lee & Krashen, 1996; Long & Prat, 2002; Mar, Oatley, Hirsh, dela Paz, & Peterson, 2006; Pavonetti, Brimmer, & Cipielewski, 2002–2003; Radloff, 2008; Stainthorp & Hughes, 2000), studies in which the checklist and the outcome measures were not administered within the same school year (e.g., Harlaar et al, 2007; Hood, Conlon, & Andrews, 2008; Shatil & Share, 2003; Stainthorp, 1997), and studies in which the participants were too old to meet our inclusion criteria (e.g., Lee, Krashen, & Tse, 1997; Stone, Fisher, & Eliot, 1999; West et al, 1993). Studies were also excluded when the respondents were teachers (e.g., McCutchen et al, 2002), kindergarten children (e.g., Bulat, 2005), or the parents of school-aged children (e.g., McGrath et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…We excluded print exposure studies that reported no child outcomes or outcomes other than comprehension and technical reading and spelling skills, such as science tests or social ability tasks (e.g., Bråten et al, 1999; Burgess, 2005; Castles, Datta, Gayan, & Olson, 1999; Chomsky, 1972; Curry, Parrila, Stephenson, Kirby, & Catterson, 2004; Korat & Schiff, 2005; Lee & Krashen, 1996; Long & Prat, 2002; Mar, Oatley, Hirsh, dela Paz, & Peterson, 2006; Pavonetti, Brimmer, & Cipielewski, 2002–2003; Radloff, 2008; Stainthorp & Hughes, 2000), studies in which the checklist and the outcome measures were not administered within the same school year (e.g., Harlaar et al, 2007; Hood, Conlon, & Andrews, 2008; Shatil & Share, 2003; Stainthorp, 1997), and studies in which the participants were too old to meet our inclusion criteria (e.g., Lee, Krashen, & Tse, 1997; Stone, Fisher, & Eliot, 1999; West et al, 1993). Studies were also excluded when the respondents were teachers (e.g., McCutchen et al, 2002), kindergarten children (e.g., Bulat, 2005), or the parents of school-aged children (e.g., McGrath et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…One of this study's important contributions to education and psycholinguistic research is its use of schoolbook borrowing as a measure of reading amount, as well as its comparison to TRT, which has been used with elementary school students in many previous studies (Cunningham & Stanovich, 1990;Echols et al, 1996;Korat & Schiff, 2005). The correlation between these variables was positive, but it was relatively small and not significant, r = .18 (p > .10).…”
Section: Comparison Of Schoolbook Borrowing and Trtmentioning
confidence: 94%
“…There are some suggestions to help students master the skills of writing:  Reading various types of material and scientific literature that shaped as a hobby and enjoyable activities. According to Korat & Schiff [9] in model developed by Shanahan and Lomax, writing knowledge has a small or almost no effect on reading but reading knowledge has a very enormous effect on writing. It shows that reading is a vital component on giving the greater impact on writing skills.…”
Section: Writing Skillsmentioning
confidence: 99%
“…Students who sit in all grade levels strive with writing difficulties including those in elementary school [9]; [10]; [18]. But they possibly do make an effort to give a "good writing" essay as they understand it [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation